The utility of exhaled nitric oxide in patients with suspected asthma - Martin, M.J.; Wilson, E.; Gerrard-Tarpey, W.; Meakin, G.; Hearson, G.; McKeever, T.M.; Shaw, D.E.; Harrison, T.W. (BMJ Publishing Group, 2016)
The value of FENO measurements in patients with symptoms suggestive of asthma is unclear. We performed an observational study to assess the ability of FENO to diagnose asthma and to predict response to inhaled corticosteroids (ICS). Our findings suggest FENO is not useful for asthma diagnosis but is accurate at predicting ICS response.